Kontradiksi “Division Of Labour” Menurut Ibnu Khaldun Dan Adam Smith: Kajian Perbandingan Dan Implikasinya Dalam Ekonomi - Setiawan Bin Lahuri; Dwi Kurnia Nurunisa; Hartomi Maulana (ITB AAS INDONESIA Surakarta, 2022)
Labor is the most important element in determining the value of an economic system. Therefore, the expertise of labor is very influential in the development of an economic industry so specialization of work is needed in the system. This theory was first proposed by Ibn Khaldun in the 14th century. However, conventional economists argue that Adam Smith is the father of all modern economic theories. So this paper aims to review the originators of the theory of division of labor and analyze its implications in industrial, social, and international economics. This study uses a qualitative method with a library research approach because this research is a historical study. The results of this study find that Ibn Khaldun is the father of world economics who preceded Adam Smith for six centuries. The implications of the division of labor theory are the increasing industrial economy, strengthening social relations between communities to advance the country's economy so that it can follow international trade.